Blood pressure lowering efficacy of angiotensin receptor blockers for primary hypertension - Heran, Balraj S (Cochrane Database Syst Rev, 2008)
BACKGROUND: Angiotensin receptor blockers (ARBs) are widely prescribed for hypertension so it is essential to determine and compare their effects on blood pressure (BP), heart rate and withdrawals due to adverse effects (WDAE). OBJECTIVES: To quantify the dose‐related systolic and/or diastolic BP lowering efficacy of ARBs versus placebo in the treatment of primary hypertension. SEARCH METHODS: We searched CENTRAL (The Cochrane Library 2007, Issue 1), MEDLINE (1966 to February 2007), EMBASE (1988 to February 2007) and reference lists of articles. SELECTION CRITERIA: Double‐blind, randomized, controlled trials evaluating the BP lowering efficacy of fixed‐dose monotherapy with an ARB compared with placebo for a duration of 3 to 12 weeks in patients with primary hypertension. DATA COLLECTION AND ANALYSIS: Two authors independently assessed trial quality and extracted data. We contacted study authors for additional information. WDAE information was collected from the trials. MAIN RESULTS: Forty six RCTs evaluated the dose‐related trough BP lowering efficacy of 9 ARBs in 13 451 participants with a baseline BP of 156/101 mm Hg. The data do not suggest that any one ARB is better or worse at lowering BP. A dose of 1/8 or 1/4 of the manufacturers’ maximum recommended daily dose (Max) achieved a BP lowering effect that was 60 to 70% of the BP lowering effect of Max. A dose of 1/2 Max achieved a BP lowering effect that was 80% of Max. ARB doses above Max did not significantly lower BP more than Max. Due to evidence of publication bias, the largest trials provide the best estimate of the trough BP lowering efficacy for ARBs as a class of drugs: ‐8 mm Hg for SBP and ‐5 mm Hg for DBP. ARBs reduced BP measured 1 to 12 hours after the dose by about 12/7 mm Hg. AUTHORS' CONCLUSIONS: The evidence from this review suggests that there are no clinically meaningful BP lowering differences between available ARBs. The BP lowering effect of ARBs is modest and similar to ACE inhibitors as a class; the magnitude of average trough BP lowering for ARBs at maximum recommended doses and above is ‐8/‐5 mmHg.  Furthermore, 60 to 70% of this trough BP lowering effect occurs with recommended starting doses. The review did not provide a good estimate of the incidence of harms associated with ARBs because of the short duration of the trials and the lack of reporting of adverse effects in many of the trials.